2021
DOI: 10.1159/000520924
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Oesophageal Squamous-Cell Carcinoma and Adenocarcinoma: A Multicentre Retrospective Cohort Study

Abstract: <b><i>Background:</i></b> Oesophageal cancer comprises 2 different histological variants: oesophageal squamous-cell carcinoma (ESCC) and adenocarcinoma (EAC). While there are multiple therapeutic options for both types, patients with advanced or metastatic oesophageal cancer still suffer from poor prognosis. <b><i>Aims:</i></b> The study aimed to examine the association between the risk of oesophageal cancer and medications and to estimate the chemopreventive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…28 Finally, 20 articles were selected for the final evaluation to investigate the association between gastric acid suppressants and the risk of developing EAC. 9 , 10 , 11 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Finally, 20 articles were selected for the final evaluation to investigate the association between gastric acid suppressants and the risk of developing EAC. 9 , 10 , 11 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…From the 20 studies in this analysis, there were 1,155,699 patients. Of these, 11 studies used a cohort design, which included 1,125,437 patients 10 , 11 , 29 , 30 , 31 , 34 , 35 , 38 , 39 , 42 , 45 and 8 studies had a case–control design, with 27,727 participants. 9 , 32 , 33 , 36 , 40 , 41 , 43 , 44 One study was conducted as an randomized controlled trial and included 2,535 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An accumulating body of evidence strongly suggests that metformin holds promise as a chemopreventive agent. Arai et al conducted a multicenter retrospective cohort analysis to investigate the chemopreventive effects of commonly used drugs on ESCC and EAC [ 45 ]. They showed that the use of PPIs, aspirin, cyclooxygenase-2 inhibitor (COX2I), steroids, statins, and metformin was associated with a lower risk of ESCC compared to non-use.…”
Section: Metformin In Esophageal Cancer: Exploring Its Clinical Signi...mentioning
confidence: 99%
“…The type of esophageal cancer varies region, with squamous cell carcinoma comprising more than 90% of cases in Asian countries like Japan, South Korea, and China, while adenocarcinoma accounts for 50 to 70% in Europe and the United States, with squamous cell carcinoma representing about 3% to 5%. PPIs do not appear to play a protective or risk-inducing role in esophageal adenocarcinoma [13], but they may have a preventive effect in esophageal squamous-cell carcinoma [14]. Moreover, PPI use has been associated with an increased risk of pancreatic cancer, liver cancer, and biliary tract cancer [15][16][17].…”
Section: Ppis and The Risk Of Gastrointestinal Tumorsmentioning
confidence: 99%